Communication between health workers and people with sickle cell disease: integrative review (Research, Society and Development, 2022)
Objectives: to analyze the scientific evidence regarding communication between people with sickle cell anemia and health care professionals. Methodology: this is an integrative review whose search for primary studies was conducted in PubMed, LILACS, Embase and CINAHL databases. Results: pain, lack of knowledge about the disease itself, racial prejudice, and professional perception that people with sickle-cell disease are addicted to medications make communication among those involved difficult. On the other hand, adequate communication with the professional, evidence-based care, and equitable assistance contribute to a lower rate of hospitalization and readmission of people with sickle cell disease. People with higher education level are better able to understand the content of communication with the professional. Conclusion: adequate communication enables better interaction between health professionals and people with sickle cell anemia and provides a favorable environment for knowledge exchange and integral assistance, valuing individuals and meeting their needs.